2020
DOI: 10.24940/theijbm/2020/v8/i2/bm2002-042
|View full text |Cite
|
Sign up to set email alerts
|

Organisational Structure and Operational Efficiency of Selected Money Deposit Banks in Lagos State, Nigeria

Abstract: The myriad of problems facing the Nigerian financial institution today include, self-control influence, complex banking structure and weak internal control system. These have resulted into financial distress and liquidation of some banks. This has resulted in loss of confidence by customers since they have not been able to curb the ugly event called poor management of depositor's funds and internal structure (Onuba, 2017). According to Uwaleke (2017) the Nigeria justice system is very slow and, therefore, fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…The finding is also consistent with the study of Okafor et al (2017) study that organisational structure increases the productivity of their workers and organisational performance translates to business growth. Consistent with the findings of this study, Shabbir (2017) found that organisational structure (the nature of hierarchical layers and formalisation) had a significant influence on the performance of brewing firms in Nigeria.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The finding is also consistent with the study of Okafor et al (2017) study that organisational structure increases the productivity of their workers and organisational performance translates to business growth. Consistent with the findings of this study, Shabbir (2017) found that organisational structure (the nature of hierarchical layers and formalisation) had a significant influence on the performance of brewing firms in Nigeria.…”
Section: Discussionsupporting
confidence: 92%
“…The consensus is that an organization's structure must be based on its objectives. According to studies by Okafor, Kalu, and Ozioma (2017), Ogosi and Agbaeze (2018), and Bekanwah et al, among others, organisational structure had a significant impact on corporate success in Nigeria (2020). Organisational effectiveness is significantly influenced by organisational structure (Ugwu, Onoh Nnadi & Udeze, 2019).…”
Section: Introductionmentioning
confidence: 99%